Study on the hydration properties of a ternary cementitious material system containing activated gold tailings and granulated blast furnace slag. (1st January 2023) - Chen, Bingjiang; Pang, Lufeng; Zhou, Zaibo; Chang, Qingshan; Fu, Peng
Abstract: This paper mainly studies the hydration properties of a mechanical-chemical-thermal coupling activated gold tailings (CGT)-Cement-granulated blast furnace slag (GBFS) ternary cementitious material system. The effect of the CGT-Cement-GBFS cementitious material system on the mechanical properties and porosity of the mortar is studied. The hydration heat, hydration products, calcium hydroxide (CH) content, chemically bound water (CBW) content, micromorphology and elemental compositions of the CGT-Cement-GBFS cementitious material system are tested by Isothermal calorimeter (TA), X-ray diffractometer (XRD), Thermogravimetric analysis (TGA), Differential thermal analysis (DTA), Scanning electron microscope (SEM) and Energy dispersive spectrometer (EDS). The research results show that the CGT-cement-GBFS cementitious material system delays the end time for the induction period of the paste and reduces the main exothermic peak and cumulative hydration heat but improves the early degree of hydration of cement compared with the addition of CGT and GBFS alone. The main hydration products of the CGT-Cement-GBFS cementitious material system are C–S(A)-H gel, CH, monosulfoaluminate, ettringite and monocarboaluminate, calcium aluminate hydrate. The CH content of the CGS3 (15 wt% CGT and 15% wt.% GBFS) at 56 d was 23.25% lower than that of the pure cement sample (CGS0), but the CBW content was 3.14% higher than that of CGS0. The CGT-Cement-GBFS cementitious material system generates C–S(A)-H gel with a higher Ca/Si ratio than CGS0 in the early hydration stage. As the secondary hydration reaction proceeds, the C–S(A)-H gel shows a decrease in the Ca/Si ratio. The CGT-Cement-GBFS cementitious material system can ensure the hydration degree in the early stage, and can continue hydration in the later stage, thereby improving the overall degree of hydration. The compressive strength of CGS3 at 28 d is 48.59 MPa, which is 5.36% higher than that of CGS0. The cumulative porosity of CGS3 at 56 d is 0.89 mL/g, which is 31.75% lower than that of CGS0. The CGT-Cement-GBFS cementitious material system optimizes the pore size distribution of the mortar base on physical and chemical effects, improves the compactness of the mortar, and improves the compressive strength of the mortar. This research provides a certain reference value for the practical application of gold tailings in cement-based materials. Highlights: The CGT-Cement-GBFS cementitious material system delays the end time of the induction period of the paste. The CGT-Cement-GBFS cementitious material system can improve the overall hydration degree. As the secondary hydration reaction proceeds, the Ca/Si ratio of the C–S(A)-H gel decrease. The CGT-Cement-GBFS cementitious material system optimizes the pore size distribution of the mortar.